Recruitment, retention and employment growth in the long-term care sector in England - Teo, Hansel; Vadean, Florin; Saloniki, Eirini-Christina (Frontiers in Public Health, 2022)
This paper studies the relationship between turnover, hiring and employment growth in the long-term care (LTC) sector in England and sheds light on how challenges in both recruitment and retention affect the sector's ability to meet growing demand for care services. Using the Adult Social Care Workforce Data Set (ASC-WDS), a large longitudinal dataset of LTC establishments in England, and fixed effects estimation methods we: (a) quantify the relationship between the in/outflow of care workers and the expansion/contraction of employment within establishments, (b) establish the role of staff retention policy for workforce expansion, and (c) identify the role of recruitment frictions and its impact on hiring and employment contraction. Our analysis indicates that care worker turnover and employment growth are negatively related. A one percentage point increase in employment contraction is associated with a 0.71 percentage point rise in turnover, while a one percentage point increase in employment expansion is associated with a 0.23 percentage point fall in turnover. In contrast, we find that hiring rates and employment growth are positively related. A one percentage point increase in employment expansion is associated with a 0.76 percentage point rise in hiring, while a one percentage point increase in employment contraction is associated with a 0.26 percentage point decrease in hiring. We argue that the negative turnover-employment growth relationship within expanding establishments provides evidence that better staff retention is associated with higher employment growth. Using information on establishments' annual change in vacancies, and controlling for changes in new labor demand, we also find rising year-on-year vacancies amongst establishments with declining employment. This provides evidence that recruitment frictions drive the declining rate of replacement hiring amongst contracting establishments. Across sectors, we find that the employment growth-turnover and the employment decline-hiring relationships are relatively stronger in the private and voluntary sectors compared to the public sector, suggesting that the impact of staff retention and recruitment frictions on employment is more acute in these sectors.